The Effect of Dhikr Therapy on Stress of Undergraduate Nursing Students: Siti Rifdahul Zahra, Hadi Abdillah, Lutiyah - Siti Rifdahul Zahra; Hadi Abdillah; Lutiyah (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
Stress is a common phenomenon in the global society and can be experienced by anyone, including university students, but not all individuals who experience stress pressure have the knowledge and skills to manage the stress they experience. This study aims to explore the effect of dhikr therapy as an intervention that can help college students manage stress. In this study, the population consisted of 48 S1 Nursing Level 4 students of Muhammadiyah Sukabumi University. This study used purposive sampling technique, so that 43 samples could be obtained. Based on the results of the Wilcoxon test, the resulting p-value is 0.000 <0.05, which means that there is an effect of dhikr therapy on stress in undergraduate nursing students.